La fuga de Edipo. El pliegue Deleuze-Lacan - Bustamante, Ani (2016)
This article aims to put face to face the positions of Deleuze and Lacan in relation to the theories regarding the idea of the Oedipus complex inherited from Freudian psychoanalysis. This confrontation will become manifest by reviewing the concepts of desire, repression and castration, from the point of view of the subject’s relationship with language. In order to achieve this purpose, we will go through thetopological proposals whereby both Deleuze and Lacan render account of that whichis housed outside the signifying logic, the paradigmatic axis of which is precisely the Oedipal Logic, thus forging a cutting-edge work in which the materiality of language, its sonority and texture will acquire relevance to rethink the status of the unconscious itself.